GitOps Cookbook : kubernetes automation in practice - Vinto, Natale (O'Reilly Media, 2023)
Why are so many companies adopting GitOps for their DevOps and cloud native strategy? This reliable framework is quickly becoming the standard method for deploying apps to Kubernetes. With this practical, developer-oriented book, DevOps engineers, developers, IT architects, and SREs will learn the most useful recipes and examples for following GitOps practices. Through their years of experience in application modernization, CI/CD, and automation, authors Alex Soto Bueno and Natale Vinto from Red Hat walk you through all the steps necessary for successful hands-on application development and deployment with GitOps. Once you start using the recipes in this book, you'll have a head start in development cycles on Kubernetes following the GitOps approach. You'll learn how to: Develop and deploy applications on Kubernetes Understand the basics of CI/CD and automation on Kubernetes, and apply GitOps practices to implement development cycles on the platform Prepare the app for deployment on multiple environments and/or multiple Kubernetes clusters Deploy apps for either multiple environments using GitOps and Argo CD, or for Kubernetes clusters Create Kubernetes-native pipelines with Tekton Provide and extend DevOps skills for the team working on Kubernetes Use progressive delivery to put your applications into production.